Food processing a video field trip - Blain, Frank; Learning seed (Lake Zurich, Ill. : Learning Seed, 2003)
Reveals how freeze drying enables real strawberries to end up in a cereal box. Viewers see freeze-drying, flash freezing, vacuum cooking, grain milling. Teaches some of chemistry, physics, and history of food processing.
Title from title screen
Executive producer : Jeffrey Schrank
Keywords: Food industry and trade; Food -- Preservation